The Impact Of Motivation, Compensation And Organizational Culture of The IGM Foundation on Increasing The Performance of Study Program on The STEBIS IGM - Satria, Chandra; Rofiq, Rofiq (Jurnal Pemerintahan dan Politik, 2025)
A company's organizational effectiveness is a crucial factor in determining how sustainable the company will be in the future. This article's goal is to clarify how corporate culture, pay, and motivation relate to the success of study programs at the Indo Global Mandiri Campus. The whole academic community of the Indo Global Mandiri School of Sharia Business Economics Study Program (STEBIS IGM) as well as the leadership of the Indo Global Mandiri Foundation management body made up the 50 respondents in the research sample. Using the IBM SPSS 25 statistical test, the survey approach manages quantitative data. The study's findings indicate that: Performance and motivation variables have a weak and negative association, suggesting that motivation components are less. The implications show that the factor of increasing compensation for employees will be able to have an influence on improving existing performance even though it will not have much of an impact on what is expected by the organization; Organizational culture variables have a positive and significant relationship to the performance of the STEBIS Indo Global Mandiri Study Program.